Analisis Kebijakan Pemerintah dalam Peningkatan Kesehatan Ibu dan Anak melalui Posyandu di RW 01 Kelurahan Penunggangan Utara - Septiani, Risa; Zayyaan, Ashrianni; Khikmawanto, Khikmawanto (TSAQOFAH, 2025)
Basic healthcare services play a vital role in public health development, with Posyandu serving as a strategic community-based health service facility in Indonesia. This study aims to evaluate government support for Posyandu Cemara RW 01 using a qualitative approach through in-depth interviews. The focus of the study includes the provision of medical equipment, operational funding, and cadre training. The findings reveal that while the government has provided support in the form of medical tools and operational funds, gaps remain in the area of cadre training. The limited training and human resource development have led to inadequate service delivery skills among cadres, ultimately reducing public trust in the Posyandu. These findings underscore that the effectiveness of government support has not fully addressed the needs on the ground. The study concludes by highlighting the importance of formulating more responsive and sustainable policy strategies, particularly in enhancing cadre capacity, to strengthen the role of Posyandu as a frontline institution in community healthcare delivery.